2019
DOI: 10.1021/acsami.9b08051
|View full text |Cite
|
Sign up to set email alerts
|

An Insulating Al2O3 Overlayer Prevents Lateral Hole Hopping Across Dye-Sensitized TiO2 Surfaces

Abstract: Three chromophores of the general form [Ru(bpy′) 2 (4,4′-(PO 3 H 2 ) 2 -2,2′bipyridine)] 2+ , where bpy′ is 4,4′-(C(CH 3 ) 3 ) 2 -2,2′-bipyridine (Ru(dtb) 2 P); 4,4′-(CH 3 O) 2 -2,2′-bipyridine (Ru(OMe) 2 P), and 2,2′-bipyridine (RuP) were anchored to mesoporous thin films of TiO 2 nanocrystallites at saturation surface coverages to investigate lateral self-exchange Ru III/II intermolecular hole hopping in 0.1 M LiClO 4 / CH 3 CN electrolytes. Hole hopping was initiated by a potential step 500 mV positive of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…The anisotropy decays were modeled with the previously described Monte Carlo simulations. 45,46 An intermolecular energy transfer rate constant of 4 × 10 7 s −1 was found that corresponds to ∼25 ns per energy transfer, consistent with reports of related ruthenium complexes (Figure 3B). 47 Therefore, in the absence of excited-state electron transfer, energy transfer occurs an average of 26 times within the excited-state lifetime.…”
Section: ■ Resultssupporting
confidence: 89%
“…The anisotropy decays were modeled with the previously described Monte Carlo simulations. 45,46 An intermolecular energy transfer rate constant of 4 × 10 7 s −1 was found that corresponds to ∼25 ns per energy transfer, consistent with reports of related ruthenium complexes (Figure 3B). 47 Therefore, in the absence of excited-state electron transfer, energy transfer occurs an average of 26 times within the excited-state lifetime.…”
Section: ■ Resultssupporting
confidence: 89%
“…Temperature-dependent kinetic studies made as a function of the surface coverage support the conclusion that rapid hole hopping promotes charge recombination . Taken together, these findings indicate that unwanted charge recombination can be inhibited through control of lateral hole hopping, an unexpected finding that may be further exploited in future research …”
Section: Discussion and Perspectivessupporting
confidence: 58%
“…75 Taken together, these findings indicate that unwanted charge recombination can be inhibited through control of lateral hole hopping, an unexpected finding that may be further exploited in future research. 76 2.3.3. Recombination to Acceptor−Bridge−Donor (A−B− D) Sensitizers.…”
Section: Kinetic Models and Holementioning
confidence: 99%
“…Polarized light generates an anisotropic population of interfacial states whose timedependent reactivity clearly demonstrates that hole hopping followed excited-state injection under a variety of experimental conditions. [109][110][111] Monte Carlo simulations revealed that an oxidized sensitizer could circumnavigate an entire anatase nanocrystal by hole-hopping before charge recombination occurred. 110 The discovery that hole-hopping rates were directly correlated with charge recombination kinetics represents an important finding.…”
Section: Spectroscopymentioning
confidence: 99%